Opportunities for developing neural stem cell treatments for acute ischemic stroke: A systematic review and gap analysis - Buchlak, Quinlan D; Esmaili, Nazanin; Moore, Justin (Journal of clinical neuroscience, 2024)
•3,396 articles were screened and 33 met inclusion criteria.•Many studies appeared to be at risk of bias.•Most studies were preclinical and involved stem cell administration within 24 h.•Stem cell therapy appears to be associated with beneficial effects post stroke.•A gap analysis identified numerous opportunities for treatment development. Ischemic stroke is a leading cause of disability and death. Current treatments are limited. Stem cell therapy has been highlighted as a potentially effective treatment to mitigate damage and restore function, but efficacy results are mixed. This study aimed to systematically review the literature on stem cell therapies for early acute ischemic stroke; and identify opportunities for future research to facilitate the development of an effective stem cell-based treatment. Original research published within the last 10 years that focused on the evaluation of a stem cell-based treatment for acute ischemic stroke in adult patients or subjects was included. Risk of bias was assessed using the SYRCLE and Cochrane risk of bias tools for animal and human studies, respectively. 3,396 articles were screened, 58 full-text articles were reviewed and 33 met inclusion criteria. Many studies appeared to be at risk of bias. Study designs and results were heterogeneous. Most studies were preclinical and involved stem cell administration within 24 hours. Seven studies tested the effects of multiple administration timepoints and one investigated repeat dosing. Six studies were conducted in humans and stem cell administration ranged from 24 hours to 90 days post stroke. Most studies employed the use of mesenchymal stem cells. The most appropriate cell delivery method appeared to be intra-arterial. Evidence suggests that stem cell therapy may be associated with beneficial effects. A literature gap analysis identified numerous opportunities for treatment development.